ESP Needs Analysis of Macroskills of Social Work Students - Ngo, Cristy Grace A.; Mabale, Almira Luz M.; Maspara, Carylle Maxine; Montalbo, Jury Rose C.; Alcayde, Frances Arabella B. (CV. Tripe Konsultan, 2024)
This quantitative study employed needs analysis then revealed the preferred learning aids and learning activities, and the level of proficiency in reading, listening, writing, and speaking of 50 social work students in a private academic institution. Findings revealed that students showed a strong enthusiasm for visual and audiovisual aids as learning tools and lectures and class discussions as learning activities. Moreover, among the four macro skills, the students excel in reading comprehension at C1 level but face challenges in the affective domain; writing skills at B1 level, with strengths in content but struggles in organization; listening proficiency at B2 level, highlighting difficulties with accents and vocabulary; and speaking skills range from A2 to B1 levels, with stronger interaction skills at B2 level, indicating a need for improvement in fluency and coherence. These insights suggest that the social work students are capable of simple communicative English and are more inclined toward traditionalist and conceptual learning. Furthermore, students need more application activities that showcase their listening and speaking skills, as well as more contextualized and immersive learning activities and aids that incorporate variation and encourage spontaneous production.